2023
DOI: 10.1021/acs.joc.2c03078
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)-Catalyzed Regioselective Synthesis of Electron-Rich Benzothiazoles from Aryl Isothiocyanates via C–H Functionalization

Abstract: We report herein a direct synthetic route for the preparation of 2-arylbenzothiazoles using aryl isothiocyanates and electron-rich arenes. The synthetic route involves triflic acid promoted addition of the arenes to aryl isothiocyanates followed by FeCl3-catalyzed C–S bond formation via C–H functionalization. The approach provides the advantage of synthesis of benzothiazoles without the conventional use of aryl aldehyde/carboxylic acid precursors employing the less expensive iron(III) catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…The same group in the following year reported a catalystfree cascade approach for the synthesis of highly functionalized tetrahydroquinazolines ( 59) by reacting 2-aminophenylacrylates (57) with isothiocyanates (58). This atom economic methodology proceeds via amidation and concurrent chemoselective Michael-addition (Scheme 24).…”
Section: B Cyclisation Involving Azomethine Linkagementioning
confidence: 99%
See 1 more Smart Citation
“…The same group in the following year reported a catalystfree cascade approach for the synthesis of highly functionalized tetrahydroquinazolines ( 59) by reacting 2-aminophenylacrylates (57) with isothiocyanates (58). This atom economic methodology proceeds via amidation and concurrent chemoselective Michael-addition (Scheme 24).…”
Section: B Cyclisation Involving Azomethine Linkagementioning
confidence: 99%
“…Alla et al reported a FeCl 3 -catalyzed regioselective synthesis of 2-arylbenzothiazoles ( 115 ) via C–H bond functionalization. 58 Initially, the protocol selectively forms C–C bond at the para position of the anisole ( 114 ) with isothiocyanates ( 113 ) which is followed by a FeCl 3 catalyzed C–S bond formation. The protocol provides a convenient pathway for the synthesis of benzothiazole in moderate to good yields under mild reaction conditions without using aryl aldehyde/carboxylic acid precursors (Scheme 49).…”
Section: Reactivity Of Alkyl/aryl Itcsmentioning
confidence: 99%
“…From the experimental findings and literature survey, a mechanistic pathway has been proposed ( Scheme Very recently, Srinivas and coworkers [172] in 2023 developed an efficient synthetic route for the synthesis of biologically important scaffolds benzothiazoles 155 via one-pot tandem reaction in a highly regioselective manner, starting from easily accessible functionalized phenyl isothiocyanates 194 and electron-rich substituted aromatic moiety 195 in the presence of FeCl 3 , Na 2 S 2 O 8, and DCE as solvent at 70 °C (Scheme 150). This synthetic methodology involves the triflic acid-mediated addition of aromatic moiety 195 to the phenyl isothiocyanates 194, followed by iron (III)-catalyzed carbon-sulfur bond formation via CÀ H activation.…”
Section: The Protocols To Access Benzimidazoles and Their Derivatives...mentioning
confidence: 99%
“…Initially, the previously reported techniques for the synthesis of benzo [b]thiophene have been reported in literature due to their signi cance [31][32][33][34][35][36][37][38][39]. There are numerous prospects for the development of environmentally friendly and sustainable protocols for organic synthesis because solar energy (visible light) is a pure, easy-to-use, and limitless energy source [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%